2014
DOI: 10.1055/s-0033-1360220
|View full text |Cite
|
Sign up to set email alerts
|

Isobolographic Analysis of the Antinociceptive Interaction between Ursolic Acid and Diclofenac or Tramadol in Mice

Abstract: It is considered that natural products used in folk medicine can potentiate the effect of drugs. The aim of this study was to evaluate the pharmacological interaction between ursolic acid, a triterpene isolated from herbal medicines to treat pain, and the analgesics diclofenac or tramadol. Individual dose-response curves of the antinociceptive effect of these compounds were built to calculate the ED50, as well as the pharmacological interaction, by using isobolographic analysis. All treatments decreased signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 30 publications
(43 reference statements)
1
18
0
Order By: Relevance
“…As shown in Table 6 , arjunolic acid, cyclocaric acid B, pterocaryoside B and pterocaryoside A were found to be abundant in all samples. In addition, cyclocaric acid B, pterocaryoside B and pterocaryoside A were unique constituents detected from C. paliurus leaves, which can be used as characteristic compounds to identify the authenticity of this plant [ 14 , 15 , 16 , 17 ]. Our results showed that the samples from Jiangxi Province (S14 and S15) contained the highest levels of the detected triterpenoid components, followed by the samples from Liping of Guizhou province (S6) and Jianghua of Hunan Province (S10).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 6 , arjunolic acid, cyclocaric acid B, pterocaryoside B and pterocaryoside A were found to be abundant in all samples. In addition, cyclocaric acid B, pterocaryoside B and pterocaryoside A were unique constituents detected from C. paliurus leaves, which can be used as characteristic compounds to identify the authenticity of this plant [ 14 , 15 , 16 , 17 ]. Our results showed that the samples from Jiangxi Province (S14 and S15) contained the highest levels of the detected triterpenoid components, followed by the samples from Liping of Guizhou province (S6) and Jianghua of Hunan Province (S10).…”
Section: Resultsmentioning
confidence: 99%
“…Acetonitrile was of HPLC grade from Tedia (Fairfield, OH, USA); deionized water was further purified by a Milli-Q purification system (Millipore, Millford, MA, USA); HPLC-grade formic acid was purchased from Aladdin Co., Ltd. (Shanghai, China), and other reagents were all of analytical reagent grade. The reference standards of 3- O -caffeoylquinic acid, 4- O -caffeoylquinic acid, 4,5-di- O -caffeoylquinic acid, quercetin-3- O -glucuronide, quercetin-3- O -galactoside, isoquercitrin, kaempferol-3- O -glucuronide, kaempferol-3- O -glucoside, quercetin-3- O -rhamnoside, hederagenin and oleanolic acid were purchased from Shanghai Yuanye Biotechnology Co., Ltd. (Shanghai, China), and arjunolic acid was purchased from BioBioPha Co., Ltd. (Kunming, China), whereas kaempferol-3- O -rhamnoside, cyclocaric acid B, pterocaryoside A and pterocaryoside B were isolated and purified previously from the leaves of C. paliurus in the laboratory of China Pharmaceutical University (Nanjing, China) and were elucidated by comparison of spectral data (UV, MS, 1 H-NMR, 13 C-NMR) with those of published references [ 16 , 17 ]. The purity of each compound was determined to be more than 98% by normalization of the peak area detected by HPLC–UV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our study is the first report on the antagonistic activity of tramadol and tizanidine in acute inflammatory pain. However, previous studies have reported that tramadol has shown an antagonistic interaction effect with metamizol [Poveda et al., ], rofecoxib [García‐Hernández et al., ], dexketoprofen [Miranda et al., ], pregabalin [Keyhanfar et al., ], and ursolic acid [Déciga‐Campos et al., ]. The mechanism underlying these antagonistic interactions remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The UA drug was extracted from many plants such as the whole grass of the Labiatae plant, Prunella vulgaris, and the leaves of the holly, holly, iron holly leaves [33]. The UA is a triterpenoid compound found in natural plants and has many biological effects such as sedative [34], anti-in ammatory [35], antibacterial [36], and immune defense responses [37]. The Ursolic acid (UA), also promote osteoblast differentiation and new bone formation.…”
Section: Morphologies and Structures Of Mhap Nanoparticlesmentioning
confidence: 99%